FORMATION OF INDEPENDENT THINKING AMONG YOUNG PEOPLE – TODAY IS THE MOST RELEVANT DAY IN PEDAGOGY AS A FUNCTION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article is devoted to development of independent thinking in young people. The interactive methods through which is formed a creative, independent thinking are offered.